Strategic Lowering of LDL-cholesterol Post Ischemic Stroke: Identifying Optimal Targets, Timing, and Therapeutic Approaches - Kolios, Nikolaos Gavriil; Barkas, Fotios; Ntaios, George; Milionis, Haralampos (Thrombosis and Haemostasis, 2025)
Stroke remains a leading cause of morbidity and mortality worldwide, with ischemic stroke dominating the landscape. Dyslipidemia, particularly elevated low-density lipoprotein cholesterol (LDL-C), is a critical modifiable risk factor in both primary and secondary prevention of stroke. While statins have established their role in stroke prevention, questions remain regarding optimal treatment strategies for specific patient groups, the role of non-statin therapies, and lipid level targets for maximal benefit. Emerging evidence underscores the potential of novel lipid-lowering agents, namely, PCSK9 injectable therapies targeting PCSK9, bempedoic acid, and icosapent ethyl, to complement statins in specific patient groups, including those with statin intolerance, those needing further LDL reduction, and those at high residual risk because of high triglycerides. Furthermore, the variability in stroke subtypes and patient comorbidities highlights the need for individualized, evidence-based approaches to lipid management. This narrative review provides a comprehensive overview of available lipid-lowering therapies for post-stroke patients, proposing practical algorithms for “who” to treat, “how” to treat them, and “how much” LDL-C reduction is needed. We aim to bridge gaps between clinical evidence and practice, focusing on individualized approaches to improve outcomes in this high-risk population.
Keywords: ischemic stroke; lipid-lowering therapy; prevention; treatment targets